Rekonstruksi Objek 3D dari Multiple Images - Rachmawati; Risanuri Hidayat; Sunu Wibirama (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
3D reconstruction is a task of recovering 3D geometry and color information. There are two categories of 3D object reconstruction: active method, 3D model acquisition can be performed by laser scanner or structured light. Passive methods, reconstruct 3D models by image sequences from a single camera or multiple cameras. Object scanning often demand expensive equipment and special skill to operate. As a simple and low cost approach, 3D reconstruction based images became more popular among the researches. In this study apply passive reconstruction technique, the reconstruction of 3D objects made using images taken from different viewpoint leading to the same object using a digital camera.To determine the corresponding points of the two views used epipolar geometry and Direct Linear Triangulation algorithm (DLT). All required parameters are extracted from the image itself, without any calibration of the camera before. The reconstruction process can divided into four part: first, feature point extraction. Second estimate the fundamental matrix from point correspondences, third compute the camera matrix, and the end compute 3D point from image points. All the required parameters are recovered from the images. As objects of experiment used a miniatur of a statue. Experiment result show the residual error from estimation fundamental matrix is 9.9051 x10-04, and reprojection error 1.714 x 10-03 pixel. Visually, the reconstructed 3D model reseamble the shape of the original object.